Microstructure and mechanical properties of Al/steel dissimilar welds fabricated by friction surfacing assisted friction stir lap welding - Zhou, Li; Yu, Mingrun; Liu, Baiyang; Zhang, Zili; Liu, Shuwei; Song, Xiaoguo; Zhao, Hongyun (Journal of Materials Research and Technology, 2020)
Al/steel dissimilar welds were obtained by friction stir lap welding (FSLW) with an Al interlayer, which was fabricated by friction surfacing (FS). In present study, the tool pin was totally plunged into the Al plate and interlayer without stirring steel, which avoided the tool wear. The Al plate and interlayer were remarkably intermixed as pin length increased. A diffusion layer, instead of the intermetallic layer, was found at the Al/steel interface, indicating the enhanced atomic migration and related interfacial bonding. The maximum failure load of the joints of 2.8kN was reached when the 2.5mm pin tool was used. The heterogeneous microstructure, which was caused by the intermixing, was responsible for the fracture, according to the fracture profiles. Necking and dimples were depicted from the fractographies, indicating that the joints were failed by plastic fracture.